Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3122/jabfm.2009.05.080093
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cinnamon for Lowering Hemoglobin A1C in Patients with Type 2 Diabetes: A Randomized, Controlled Trial

Abstract: Purpose: Multiple trials in the past have shown conflicting results of whether cinnamon lowers glucose or hemoglobin A1C (HbA1C). The purpose of this study was to determine whether cinnamon lowers HbA1C in patients with type 2 diabetes. I performed a randomized, controlled trial to evaluate whether daily cinnamon plus usual care versus usual care alone lowers HbA1c.Methods: I randomized 109 type 2 diabetics (HbA1C >7.0) from 3 primary care clinics caring for pediatric, adult, and geriatric patients at a United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(190 citation statements)
references
References 12 publications
4
173
2
3
Order By: Relevance
“…Also Deng et al [34] have shown that resveratrol, an ingredient of Polygonum cuspidatum and red wine did enhance glucose uptake and GLUT4 movement to the CM in C2C12 myotubes. However, other in vivo, ex vivo studies and human trials which have been explored antidiabetic effect or mechanism by which cinnamon exert antidiabetic effect all are in accordance with our study results [14,16,[35][36][37][38]. But studies for cinnamon effect on the GLUT4 transcription and/or its intracellular movement in conjunction to signaling pathways are rare and the mechanism of its components is under investigation.…”
Section: Resultssupporting
confidence: 75%
“…Also Deng et al [34] have shown that resveratrol, an ingredient of Polygonum cuspidatum and red wine did enhance glucose uptake and GLUT4 movement to the CM in C2C12 myotubes. However, other in vivo, ex vivo studies and human trials which have been explored antidiabetic effect or mechanism by which cinnamon exert antidiabetic effect all are in accordance with our study results [14,16,[35][36][37][38]. But studies for cinnamon effect on the GLUT4 transcription and/or its intracellular movement in conjunction to signaling pathways are rare and the mechanism of its components is under investigation.…”
Section: Resultssupporting
confidence: 75%
“…In a randomized, uncontrolled trial of patients (n = 109) with diabetes who were on a diet and exercise regimen, treatment with cinnamon (1 g) for 90 days lowered HbA1c levels in the test group (0.83%) relative to the control group (0.37%) [9]. The decrease observed was small but statistically significant and, therefore, medically as even small decreases in HbA1c are associated with significant reductions in diabetes comorbidities.…”
Section: Presl (Lauraceae)mentioning
confidence: 99%
“…All women will be given a seven-day course of antibiotic prophylaxis, including one dose of oral azithromycin (1 g) upon admission plus intravenous ampicillin (2 g every 6 h) for 48 hours, followed by oral amoxicillin (500 mg every 8 h or 875 mg every 12 h) for the remaining five days, 26,27 and all patients will receive a full course of steroids for fetal lung maturation. After completing their stay in the labor and delivery area, patients will be transferred to the high-risk floor.…”
Section: Data Collectionmentioning
confidence: 99%